IMPACT OF INNER LIMITING MEMBRANE PEELING ON VISUAL RECOVERY AFTER VITRECTOMY FOR PRIMARY RHEGMATOGENOUS RETINAL DETACHMENT INVOLVING THE FOVEA. Issue 5 (May 2019) - Garweg, Justus G.; Deiss, Mario; Pfister, Isabel B.; Gerhardt, Christin
Abstract : Purpose: To assess the impact of inner limiting membrane peeling during vitrectomy for macula-involving retinal detachment on best-corrected visual acuity (VA). Methods: Retrospective analysis of 89 eyes with primary macula-involving retinal detachment, which was undergoing vitrectomy, endolaser, retinotomy, endodrainage, and SF6 tamponade. Membrane-blue-assisted membrane peeling had been performed in 61 of the eyes (Group 1) but not in the other 28 (Group 2), which served as controls. Results: Age, lens status, and incidence of proliferative vitreoretinopathy 26.2% versus 39.3%; P = 0.23 in the 2 groups were comparable. The preoperative visual acuity (Early Treatment Diabetic Retinopathy Study letters) was 25.7 ± 27.9 in Group 1 and 28.8 ± 29.9 in Group 2 ( P = 0.47). After surgery, these rose from 62.3 ± 30.5 (Group 1) and 34.2 ± 35.8 (Group 2) after 1 week ( P = 0.090), through 83.1 ± 8.0 and 57.2 ± 32.4 at 1 month ( P = 0.0005), to 92.1 ± 4.5 and 74.4 ± 23.1 Early Treatment Diabetic Retinopathy Study letters after 6 months ( P = 0.0005). More than 6-month incidences of proliferative vitreoretinopathy (13.1% vs. 28.6%; P = 0.13) were similar, whereas the redetachment rate (9.8% vs. 32.1%; P = 0.014), the incidence of secondary epiretinal membranes (1.6% vs. 35.7%; P = 0.0005), and the revitrectomy rate were lower in group 1 (9.8% vs. 53.6%; P = 0.0005). Conclusion: Inner limiting membrane peeling during vitrectomy for macula-involving retinal detachment may substantially contribute to the visual recovery, reducing the incidence of secondary epiretinal membrane formation. Abstract : Eyes with macula-involving retinal detachment have a limited functional prognosis. Inner limiting membrane peeling during primary vitrectomy for macula-involving retinal detachment may substantially contribute to the visual recovery and reduce the incidence of secondary epiretinal membrane formation.